Third‐Party Logistics: A Meta‐Analytic Review and Investigation of its Impact on Performance. Issue 1 (January 2014) - Leuschner, Rudolf; Carter, Craig R.; Goldsby, Thomas J.; Rogers, Zachary S.
<x xml:space="preserve">Abstract</x> Interest in third‐party logistics has been steadily increasing over the last two decades. Recently, increased focus by researchers has produced a solid literature base of academic research. In this article, a meta‐analytic approach is employed to provide a quantitative review of the empirical literature and examine relevant constructs. Fifty‐four samples across 69 peer‐reviewed journal articles, yielding a total of 9, 386 observations, were obtained and analyzed. We used transaction cost economics and the resource‐based view as lenses to hypothesize a structural model of the relationships between relational governance structure, logistics customer service, and firm performance. Additional relationships were also found and analyzed, helping to clarify the mixed existing findings in the literature. The study concludes by mapping out future directions for 3PL research, based on the study's findings.